Les principautés du Delta au temps de l'anarchie libyenne : études d'histoire politique - Yoyotte, Jean, (Recherches d'Archeologie de Philologie et d'Histoire ;, 2012)
"Jean Yoyotte's monograph, Les principautés du Delta au temps de l'anarchie libyenne (1961) provided a full reappraisal, based on a wide and rigorously analysed body of material, of an obscure chapter of Late Period history" -- Back cover.